How is the Implementation of Business Analytics in Asia? - Genesis Sembiring Depari (PT FORMOSA CENDEKIA GLOBAL, 2024)
It addresses the unique challenges and strategies of business analytics adoption across the Asian diversity, drawing on the findings of 30 academic publications. It recognizes that for Asian enterprises, Data-driven culture in collectivist and hierarchy-based cultural dynamics requires good leadership buy-in and cross-functional collaboration. Moreover, the diverse regulatory landscape of the region requires customized data governance frameworks to comply with local privacy regulations and establish confidence among stakeholders. As companies across Asia level up their data adoption, organisations need to focus on scalable technology, build a workforce which is data-literate, develop a flexible compliance framework, enable cross-functional collaboration, engage local experts and build an ethical data culture, the study noted. By The findings serve to enhance comprehension of how analytics can be implemented across the Asian context, emphashighlightening the need for a flexible and contextatively approach in addressing the unique technological, cultural and institutional landscapes of the region.